Intimate partner violence against ever-partnered women in Europe: Prevalence and associated factors—Results from the violence against women EU-wide survey - Barbier, Alice; Chariot, Patrick; Lefèvre, Thomas (Frontiers in Public Health, 2022)
Study questions: To describe prevalence of physical, sexual, and psychological intimate partner violence (IPV) against women in European Union (EU) and to search for their determinants among demographic, socioeconomic, health-related factors, and partner characteristics. Methods: Observational study. Data from the Violence against women survey, the first study conducted in the EU, which simultaneously measured all dimensions of IPV and many characteristics. The EU Agency for Fundamental Rights randomly conducted face-to-face interviews among the 28 countries with 42002 women aged 18 to 74 who resided in the survey country and spoke the language. IPV defined by a positive answer to at least one question about physical, sexual, or psychological violence perpetrated by a current or ex-partner. Findings: Among the 40357 women having already been in a relationship, 51•7% (51•2 to 52•2) reported having been victims of violence in their lifetime. Prevalence of physical, sexual, and psychological IPV were respectively 20•0% (19•6 to 20•4), 8•4% (8•2 to 8•7), and 48•5% (48•1 to 49•0). Women who were younger, employed, had a high qualified work, at least one immigrant parent, lived in an urban setting, were unmarried, separated, divorced, widowed, childlessness, cohabited with partner and others over the age of 18, had a worse self-perceived health or a history of violence before the age of 15 were more likely to report IPV. It was the same when their partners had a lower level of education, no work, were home staying, earned less than they did, were involved in one to ten years relationship, were frequently drunk, or violent otherwise. Major implication: Lifetime prevalence of reported IPV among women in Europe is high and likely underestimated. Results emphasize the importance of a comprehensive definition of IPV as well as partners characteristics. They highlight socioeconomic differences as well as poorer health status for victims of IPV.